Measuring the Potential of Local Green Growth An Analysis of Greater Copenhagen - Martinez-Fernandez, Cristina (OECD Local Economic and Employment Development (LEED) Papers, 2013)
As the need to address the impacts of climate change becomes more urgent and the subsequent green momentum continues to gather pace, individual governments and companies are transitioning to a low-carbon economy. This transition to a low-carbon economic and industrial future is taking place in a highly uncertain and competitive marketplace. With many countries and cities seeking to give their own domestic companies a head start as closer attention is paid to this low carbon transition, indicators are becoming increasingly important as a mechanism to inform the development of programmes designed to generate green economic growth. This paper presents, for the first time a local 'green growth' indicator framework. This indicator framework was developed from the OECD 'green growth' strategy at the national level, but modified to highlight issues of transition that are most relevant for local areas. This working paper is the first trialling of this approach, along with an indicator visualisation tool - or dashboard. The dashboard allows easy assessment of the progress of a particular local area in a number of indicator variables. The paper discussed results for the analysis of Copenhagen and its cleantech cluster